Review of: The Politics of Religious Tourism, edited by Dino Bozonelos and Polyxeni Moira - Gasparini, Maria Laura (The international journal of religious tourism and pilgrimage, 2024)
Review of: Bozonelos, D. and Moira. P. (Eds.) (2023) The Politics of Religious Tourism. Published by CABI, Oxfordshire, UK, 2023. Hardback: ISBN-13: 9781800621718, 248 pages - DOI: 10.1079/9781800621732.0000. Price: EUR 115.00 (Hardcover)